1992
DOI: 10.7326/0003-4819-116-7-540
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Aspiration of Gastric Contents in Patients Receiving Mechanical Ventilation: The Effect of Body Position

Abstract: We conclude that the supine position and length of time the patient is kept in this position are potential risk factors for aspiration of gastric contents. Elevating the head of the bed for patients who can tolerate the semirecumbent position may be a simple, no-cost prophylactic measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
274
0
17

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 648 publications
(297 citation statements)
references
References 22 publications
6
274
0
17
Order By: Relevance
“…Radionuclide studies reveal increased tracheal penetration of gastric contents when intubated patients are supine (85,159,201). Drakulovic et al found that the simple elevation of the head of bed to 45°results in dramatic reductions in VAP incidence and a trend toward reduced mortality (54).…”
Section: Preventionmentioning
confidence: 99%
“…Radionuclide studies reveal increased tracheal penetration of gastric contents when intubated patients are supine (85,159,201). Drakulovic et al found that the simple elevation of the head of bed to 45°results in dramatic reductions in VAP incidence and a trend toward reduced mortality (54).…”
Section: Preventionmentioning
confidence: 99%
“…Aspiration of gastric contents is a recognized risk factor for ventilator-associated pneumonia in critically ill patients (9)(10)(11)(12). However, more information is needed to determine the extent to which the frequency of tracheobronchial aspiration of gastric contents predisposes to pneumonia and other adverse outcomes.…”
mentioning
confidence: 99%
“…Furthermore, the isolation of the same organisms from the stomach, pharynx and endobronchial samples occurred in 32% of semirecombent patients compared with 68% of supine patients [80]. Gastro-oesophageal reflux, however, occurs irrespective of body position in mechanically ventilated patients with nasogastric tubes [81].…”
Section: Gastro-oesophageal Refluxmentioning
confidence: 99%